A poly(N, N-dimethylaminoethyl methacrylate-co-ethylene glycol dimethacrylate) monolith for direct solid-phase extraction of benzodiazepines from undiluted human urine. Issue 31 (28th July 2020) - Zhao, Tengwen; Du, Li; Zhang, Ziyang; Li, Na; Wang, Manman; Ren, Qi
Abstract : A poly( N, N -dimethylaminoethyl methacrylate- co -ethylene glycol dimethacrylate) monolith was successfully synthesized and applied for direct solid-phase extraction of benzodiazepines from undiluted urine samples. Abstract : A novel polymeric monolith using N, N -dimethylaminoethyl methacrylate as the monomer and ethylene glycol dimethacrylate as the crosslinker was successfully synthesized in a syringe and applied for direct solid-phase extraction of four benzodiazepines (bromazepam, triazolam, midazolam and diazepam) from undiluted urine samples prior to high performance liquid chromatography. The monolith was characterized by scanning electron microscopy, Fourier transform infrared spectroscopy and nitrogen adsorption–desorption experiments. Moreover, extraction parameters, including loading, washing and eluting conditions were optimized. Under the optimized conditions, the proposed method obtained linear ranges of 2.0–500 ng mL −1 with correlation coefficients ( r ) higher than 0.9997. The limits of detection (S/N = 3) and limits of quantification (S/N = 10) were 0.4–0.6 ng mL −1 and 1.4–2.0 ng mL −1, respectively. The recoveries at three spiked levels ranged from 83.7% to 103% with the intra- and inter-day precisions from 0.6–7.6% to 2.7–9.8%. The present monolith allowed direct loading of crude urine samples without any filtration or dilution step. Besides, the sorbent offered an enhancement factor of 16.7–20.6 and was stable enough for ten replicate cycles of extraction/desorption of urine samples. The developed method presented an alternative strategy for the accurate and convenient determination of benzodiazepines in urine samples.